Bat airway epithelial cells: a novel tool for the study of zoonotic viruses. - Isabella Eckerle (Public Library of Science (PLoS), 2014)
Bats have been increasingly recognized as reservoir of important zoonotic viruses. However, until now many attempts to isolate bat-borne viruses in cell culture have been unsuccessful. Further, experimental studies on reservoir host species have been limited by the difficulty of rearing these species. The epithelium of the respiratory tract plays a central role during airborne transmission, as it is the first tissue encountered by viral particles. Although several cell lines from bats were established recently, no well-characterized, selectively cultured airway epithelial cells were available so far. Here, primary cells and immortalized cell lines from bats of the two important suborders Yangochiroptera and Yinpterochiroptera, Carollia perspicillata (Seba's short-tailed bat) and Eidolon helvum (Straw-colored fruit bat), were successfully cultured under standardized conditions from both fresh and frozen organ specimens by cell outgrowth of organ explants and by the use of serum-free primary cell culture medium. Cells were immortalized to generate permanent cell lines. Cells were characterized for their epithelial properties such as expression of cytokeratin and tight junctions proteins and permissiveness for viral infection with Rift-Valley fever virus and vesicular stomatitis virus Indiana. These cells can serve as suitable models for the study of bat-borne viruses and complement cell culture models for virus infection in human airway epithelial cells.